Severe retinopathy of prematurity with retinal detachment in monozygotic twins. Issue 3 (18th June 2013) - Fujioka, Kazumichi; Morioka, Ichiro; Honda, Shigeru; Tsukahara, Yasutomo; Miwa, Akihiro; Shibata, Akio; Tanimura, Kenji; Yokoyama, Naoki; Yamada, Hideto; Iijima, Kazumoto
Abstract We report a monochorionic diamniotic twin pair born at 29 weeks of gestation in which both twins developed severe retinopathy of prematurity (ROP) with retinal detachment. The pregnancy was terminated due to reversal of donor‐recipient phenotypes in possible TTTS. Both twins had unstable cardiopulmonary status during the first week, and developed chronic lung disease. The larger twin, born at 1372 g, developed stage 4a ROP in both eyes, and the smaller twin, born at 1168 g, developed stage 4a ROP in the left eye. Genetic analysis of NDP, FZD4, LRP5, TSPAN12 genes revealed no mutations; however, VEGF gene polymorphism analysis showed heterozygous carrier state of the VEGF 936T allele in both twins, which is a risk factor for threshold ROP in Japanese newborn infants. We speculate the synergistic effects of unstable perinatal cardiopulmonary status and genetic predisposition due to VEGF 936C>T polymorphism caused the development of severe ROP with retinal detachment.